Approximation of the set of trajectories of the nonlinear control system with limited control resources - Huseyin, Nesir; Huseyin, Anar; Guseinov, Khalik (Mathematical Modelling and Analysis, 2018)
In this paper the control system described by a Urysohn type integral equation is studied. It is assumed that the control functions have integral constraint. Approximation of the set of trajectories generated by all admissible control functions is considered. Step by step way, the set of admissible control functions is replaced by a set consisting of a finite number of control functions which generates a finite number of trajectories. An evaluation of the Hausdorff distance between the set of trajectories of the system and the set, consisting of a finite number of trajectories is obtained.